Role of Phosphodiesterase Inhibitors in Improving Urodynamic Parameters in Patients with Spinal Cord Injury: A Preliminary Report - Iqbal, Muzzain; Chhiber, Sarbjit Singh; Wazir, Baldev Singh; Ramzan, Altaf Umar; Wani, Mohammad Saleem (Indian Journal of Neurosurgery, 2020)
Objective To analyze role of phosphodiesterase 5 (PDE5) inhibitors on urodynamic parameters in patients with suprasacral spinal cord injury.Materials and Methods This was a prospective observational hospital-based study conducted on a cohort of patients, aged between 18 and 65 years with suprasacral spinal cord injury, who were registered in Department of Neurosurgery/Urology. Cutoff period since injury was 2 years. After taking consent, baseline urodynamic study was performed, which was repeated 2 hours after taking single oral dose of 20 mg tadalafil. Urodynamic parameters such as maximum detrusor filling/voiding pressures, maximum bladder capacity, and bladder compliance before and after taking drug were compared for final results and conclusion.Results Following administration of 20 mg of tadalafil, maximum bladder capacity in mL showed statistically significant improvement from 268.39 ± 130.0 to 298.55 ± 112.0.(p < 0.05). Bladder compliance improved from 18.68 ± 6.4 to 20.25 ± 7.5 mL/cm H2O (p > 0.05). Maximum detrusor filling pressure improved from 36.03 ± 20.54 to 32.90 ± 16.47 cm H2O (p > 0.05). Maximum detrusor voiding pressure improved from 64.65 ± 33.19 to 58.13 ± 20.7 cm H2O (0 > 0.05). In patients with injury above D6 spinal cord level, statistically significant improvement was seen in maximum bladder capacity and bladder compliance after 2 hours of single oral dose of tadalafil (p < 0.05).Conclusion Our study suggests a positive role of PDE inhibitors in improving urodynamic parameters in patients with suprasacral spinal cord injury with improvement in parameters such as bladder capacity, detrusor pressures, and bladder compliance. Because this is a small study group, more studies such as this are required to reach to final conclusion.
Keywords: suprasacral spinal cord injury; phosphodiesterase 5 inhibitors; lower urinary tract symptoms; urodynamic parameters